2014
DOI: 10.1080/02640414.2014.889845
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal pressures during activity in women using an intra-vaginal pressure transducer

Abstract: Strenuous physical activity has been linked to pelvic floor disorders in women. Using a novel wireless intra-vaginal pressure transducer, intra-abdominal pressure was measured during diverse activities in a laboratory. Fifty-seven women performed a prescribed protocol using the intra-vaginal pressure transducer. We calculated maximal, area under the curve and first moment of the area intra-abdominal pressure for each activity. Planned comparisons of pressure were made between levels of walking and cycling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 21 publications
(32 reference statements)
3
54
2
Order By: Relevance
“…Data from the WIVT was found to correlate well with the simultaneous measurement of a rectal balloon catheter for coughing and Valsalva maneuvers in a clinical laboratory setting [8]. Using the WIVT, we recently monitored IAP in 57 women during standardized exercise sessions to describe maximal IAP, area under the curve, and first moment of the area of IAP during 31 activities performed in an exercise science laboratory [9]. Although this study provided the basis for wirelessly monitoring IAP, the base station transceiver required a laptop limiting the range of activity to within a 5 meter radius.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the WIVT was found to correlate well with the simultaneous measurement of a rectal balloon catheter for coughing and Valsalva maneuvers in a clinical laboratory setting [8]. Using the WIVT, we recently monitored IAP in 57 women during standardized exercise sessions to describe maximal IAP, area under the curve, and first moment of the area of IAP during 31 activities performed in an exercise science laboratory [9]. Although this study provided the basis for wirelessly monitoring IAP, the base station transceiver required a laptop limiting the range of activity to within a 5 meter radius.…”
Section: Introductionmentioning
confidence: 99%
“…Using the average and standard deviation of sit-to-stand mean max values from a previous study [20], we determined that a discernible difference of 10 cm H 2 O could be detected in 20 people with 2-sided tests, assuming α = 0.05 and power of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…Our group also recently recorded IAP in 57 women during a standard exercise session which included sit-to-stand activity and found that this produced a moderate increase in IAP with significant variability [20]. …”
Section: Introductionmentioning
confidence: 99%
“…According to Shaw et al [4], the intra-abdominal pressure rises with increasing intensity of the activity; for example, walking at an inclination of 7% results in an intra-abdominal pressure of 35 cm H 2 O compared with 66.5 cm H 2 O for running and 41.6 cm H 2 O for cycling. In this case, strenuous exercise can lead to overload and weakening of the pelvic floor muscles [3], as well as muscle fatigue immediately after the activity [6].…”
Section: Discussionmentioning
confidence: 99%
“…This fact might be explained by pelvic floor muscle weakness in situations of increased intra-abdominal pressure [3]. Furthermore, Shaw et al [4] reported a progressive increase in intra-abdominal pressure with more intense exercises. According to Da Roza [5], this type of exercise requires an increase in the contraction strength of the pelvic floor muscles to close the urogenital hiatus and to maintain urinary continence.…”
Section: Introductionmentioning
confidence: 99%